2012
DOI: 10.5897/jmpr12.031
|View full text |Cite
|
Sign up to set email alerts
|

Down regulation of matrix metalloproteinases by spearmint extract in Wehi-164 cells

Abstract: Tumor invasion and metastasis are the main causes of cancer death. Matrix metalloproteinases (MMPs) are endopeptidases which degredate the extracellular matrix proteins. MMPs have an important role in tumor progression and metastasis. Fibrosarcoma has been recognized as a highly metastatic cancer which its current therapeutic methods have not been very successful. Medicinal plants are widely used in treatment of cancers. Spearmint is a herb with well known anti-tumor activities. In the present study, the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
(56 reference statements)
0
2
0
Order By: Relevance
“…Hep2 cells showed less sensitivity than the other two cell lines [ 150 ]. Differently, aqueous extract of M. spicata showed cytotoxicity effect on U937 leukemia cells (IC 50 = 4.8 mg/mL) [ 151 ]. The methanolic extract of M. longifolia at a concentration >0.5 µg/µl demonstrated antiproliferative effects in adrenocortical tumor cell lines, with modulating activity on MAPK and PI3k/Akt pathways [ 152 ].…”
Section: Properties Of the Mentha Genusmentioning
confidence: 99%
See 1 more Smart Citation
“…Hep2 cells showed less sensitivity than the other two cell lines [ 150 ]. Differently, aqueous extract of M. spicata showed cytotoxicity effect on U937 leukemia cells (IC 50 = 4.8 mg/mL) [ 151 ]. The methanolic extract of M. longifolia at a concentration >0.5 µg/µl demonstrated antiproliferative effects in adrenocortical tumor cell lines, with modulating activity on MAPK and PI3k/Akt pathways [ 152 ].…”
Section: Properties Of the Mentha Genusmentioning
confidence: 99%
“…Mentha species exhibited modulatory effects on the expression or activity of some MMPs, and Liu et al reported that 10, 30, and 100 mg/kg of spearmint oil significantly decreased the expression of TNF-α, IL-1β, and MMP-9 in rat lung tissues [ 180 ]. Moreover, treatment of Wehi-164 fibrosarcoma cells with aqueous extract of spearmint led to significant reduction in MMP-2/MMP-9 activity in a dose-dependent manner, as there was no detectable activity of MMP-2/MMP-9 in Wehi-164 cells treated with 10 mg/mL of the extract after 24, 48, and 72 h [ 151 ]. A phytomics analysis (analysis of primary and secondary metabolites of plant extracts) showed that 500 µg/mL of M. piperita extract had significant inhibitory effect on the activity of MMP-1 (84.4%), MMP-8 (80.46%), MMP-13 (91.02%) [ 181 ].…”
Section: Properties Of the Mentha Genusmentioning
confidence: 99%